Implementation of active methodologies in the teaching-learning process in the nursing graduation course (Research, Society and Development, 2020)
The active methodology fits into the teaching practice and also has as a central proposition the learning based on problem situations influenced by critical pedagogy and they have in common the fact that they intentionally work with problems for the development of the teaching-learning processes and value learning to learn learn. This is a bibliographic research with a qualitative approach, with the objective of describing the implementation of active methodologies in the teaching-learning process in the undergraduate nursing course. After associating all descriptors, 1,389 articles were found, 1,372 were excluded and 17 articles were selected. After the reflective reading, three categories emerged: Implementation of Active Methodologies; Challenges for implementing Active Methodologies from the perspective of teaching in nursing and Contributions of Active Methodologies in the teaching-learning process of nurses in training. Active methodologies encourage students and future nurses to relate their experiences and interact on subjects and disciplines, facilitating knowledge, reflecting on a better absorption of information and, later, on a more qualified degree. This method, more interactive and innovative, also facilitates learning thanks to the immersion of scenarios very close to reality, which leads the student to reflect on the situations, stimulating him to think and develop new knowledge. It is concluded that the use of the active methodology is still a great challenge compared to the traditional model, considering that, it prevails in the structures of the current teaching. In this way, the active methodology shows itself as an alternative to this model, promoting the student's autonomy in nursing, proposing the activity instead of passivity.